Fast assessment of the critical principal stress direction for multiple separated multiaxial loadings - M. Cova; P. Livieri; R. Tovo (Fracture and Structural Integrity)
The critical plane calculation for multiaxial damage assessment is often a demanding task, particularly for large FEM models of real components. Anyway, in actual engineering requests, sometime, it is possible to take advantage of the specific properties of the investigated case. This paper deals with the problem of a mechanical component loaded by multiple, but “time-separated”, multiaxial external loads. The specific material damage is dependent from the max principal stress variation with a significant mean stress sensitivity too. A specifically fitted procedure was developed for a fast computation, at each node of a large FEM model, of the direction undergoing the maximum fatigue damage; the procedure is defined according to an effective stress definition based on the max principal stress amplitude and mean value. The procedure is presented in a general form, applicable to the similar cases.